The structural and optical properties of hydrogenated amorphous carbon (a-C:H) thin films deposited using a direct current-plasma enhanced chemical vapour deposition (DC-PECVD) technique - Abu Bakar, Suriani (2005)
Hydrogenated amorphous carbon (a-C:H) thin films were deposited using the DC plasma enhanced chemical vapour deposition (DC-PECVD) technique. The effects of the deposition parameters (chamber pressure, electrode distance, CH4 flow rate, and substrate temperature) on the deposition rate were studied. It was found that with increasing DC power, w and hence ion bombardment energy, E the deposition rate increased initially and then decreased after passing a maximum. The increase in deposition rate of the a-C:H films with increasing ion energy is explained by the increase in the concentration of dangling bond sites on the growing film surface. Further analyses which were based on the films, revealed the optimum deposition rate for every set of deposition parameters. Both power and ion bombardment energy were continuously changing during the deposition, as a results of varying deposition parameters. The films properties ranged from polymer-like (PAC) to graphite-like (GAC) a-C:H films, as the power and ion energy increased. In order to study the structure and the optical properties of a-C:H films, infrared and Raman spectroscopy, XRD, SEM, Ellipsometer, UV-Vis Spectrophotometer and photoluminescence, were used as characterization techniques to extract information on sp3/sp2 and hydrogen contents, amorphous nature, morphology, optical gap, E0, absorption coefficient, a, photoluminescence response, refractive index, n, and extinction coefficient, k, of the a-C:H films. Based on these results, the films studied in the present research are found to consist of sp2 clusters of which their size increases with increasing power and ion bombardment energy during the deposition, resulting in lower hydrogen, sp3 content and optical gap. This confirms the model proposed by Robertson where sp2 content controls the optical gap. The increase in hydrogen freed from the films at higher ion energies results in an increase in the sp2 fraction, bigger cluster size and graphitic structures of the films.